Assessmentof human dignityof the elderlyin the nursing homes - Otaghi, Masoumeh; Moghadam, Seyed Rahmatollah Mousavi; Azadi, Arman; Veisani, Yousef; Tahami, Farangis Akbari (The journal of contemporary issues in business and government, 2021)
Background and Aim: Dignity is one of the basic elements of care for the elderly and is affected by factors such as independence, privacy, patient protection and confidentiality of information. The overall purpose of this study was to determine the level of respect for human dignity of the elderly living in nursing homes in Ilam province in 2020. Materials and Methods: In a descriptive-analytical study, the views of 113 people including 54 elderly and 32 staff from two nursing homes in Ilam province and 117 graduate nursing students of Ilam University of Medical Sciences with Intrinsic Dignity Questionnaire (Shamsizadeh et al, 2018) Checked out. Data were analyzed in SPSSv-22 software by chi- square, one-way analysis of variance and univariate and multivariate linear regression. Significance level was less than 0.05. Results: The elderly were 73± 10 years old, mostly female, single, illiterate, urban, poor economic status and living in a nursing home for more than 6 months. The employees were 33± 8 years old, mostly female, single, of average economic status, university education and more than one month of work experience. Students were 34± 5 years old, mostly female, married and had at least one month of internship in each dormitory. The mean of human dignity was 157.32± 24.9 which was 168.9± 13.7 from the perspective of the elderly, 166.9± 12.9 from the staff and 122.74± 18.07 from the students (p<0.001).The average level of human dignity increased by 10.6 per person and by 22.8 per person with a longer stay (p<0.001). Conclusion: The level of respect for human dignity from the perspective of the elderly and staff was above average and from the perspective of students was below average. The most important predictors of human dignity were male gender and length of stay in the nursing home.